BENEFIT BADAN USAHA MILIK DESA TERHADAP STRUKTUR EKONOMI DAN SOSIAL MASYARAKAT - A. A. GDE PUTRA PEMAYUN (GANEC SWARA, 2023)
This study examines the "Benefits of Village Owned Enterprises to the economic and social structure of society". BUMDes is a pillar of economic activity in the village that functions as a commercial and social institution. The purpose of this study was to determine the effect of BUMDes benefits on the economic and social structure of the community in Tohpati Village, Banjarangkan District, Klungkung Regency. This study used a qualitative descriptive method, using a proportional sampling technique consisting of BUMDes managers and the community using BUMDes financial services in Tohpati Klungkung Village. Sustainable development can invite all parties, especially members of the Tohpati Klungkung Bali Village community to manage human resources to meet economic, social and other important support system needs. Maintaining sustainable development is a must for the people of Tohpati Klungkung Village because it has been proven to reduce unemployment and increase income for the community. The results of the study show that the village of Tohpati Klungkung Bali has grown rapidly as a result of BUMDes benefits being inspired by the community using financial services to increase efficiency and effectiveness in managing sources of funds and expanding employment opportunities for the work force.